Pengaruh Edukasi Discharge Planning terhadap Kemandirian Pemenuhan Kebutuhan Dasar Pasien Gagal Jantung - Devi Kristina Hutagalung; Rezqiqah Aulia Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2026)
ABSTRACT Heart failure is a chronic cardiovascular disease characterized by the inability of the heart to pump blood adequately to meet the body's metabolic demands. Patients with heart failure often experience limitations in performing activities of daily living and require continuous self-care after hospital discharge. Inadequate discharge planning may contribute to poor treatment adherence, recurrent hospitalization, and decreased independence in fulfilling basic needs. Educational discharge planning is considered an effective intervention to improve patients' understanding, self-management skills, and independence after discharge. This study aimed to determine the effect of discharge planning education on the independence of fulfilling basic needs among patients with heart failure. This study employed a quantitative pre-experimental design using a one-group pretest-posttest approach. The study involved 60 hospitalized heart failure patients selected through purposive sampling. The intervention consisted of structured discharge planning education covering medication adherence, dietary management, physical activity, symptom recognition, fluid restriction, and follow-up care. Data were collected using the Barthel Index and Self-Care of Heart Failure Index questionnaires. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Before the intervention, 61.7% of respondents demonstrated moderate independence, while only 20.0% had high independence. After receiving discharge planning education, the proportion of respondents with high independence increased to 71.7%. Statistical analysis showed a significant improvement in patients' independence after the intervention (p = 0.001). Discharge planning education significantly improves the independence of patients with heart failure in fulfilling their basic needs. Comprehensive discharge planning should become an integral component of nursing care to reduce readmission rates and improve patients' quality of life. Keywords: Discharge Planning, Heart Failure, Independence, Self-Care, Nursing Education ABSTRAK Gagal jantung merupakan penyakit kardiovaskular kronis yang ditandai dengan ketidakmampuan jantung memompa darah secara optimal sehingga kebutuhan metabolisme tubuh tidak terpenuhi. Kondisi tersebut menyebabkan pasien mengalami keterbatasan dalam melakukan aktivitas sehari-hari dan membutuhkan kemampuan perawatan diri yang baik setelah pulang dari rumah sakit. Pelaksanaan discharge planning yang belum optimal sering menyebabkan rendahnya kepatuhan terapi, tingginya angka rehospitalisasi, dan menurunnya kemandirian pasien dalam memenuhi kebutuhan dasar. Edukasi discharge planning menjadi salah satu intervensi keperawatan yang diharapkan mampu meningkatkan pengetahuan, keterampilan, dan kemandirian pasien. Penelitian ini bertujuan mengetahui pengaruh edukasi discharge planning terhadap kemandirian pemenuhan kebutuhan dasar pasien gagal jantung. Penelitian menggunakan desain kuantitatif dengan pendekatan pre-experimental one group pretest-posttest. Sampel penelitian sebanyak 60 pasien gagal jantung yang dirawat di rumah sakit dan dipilih menggunakan teknik purposive sampling. Intervensi berupa edukasi discharge planning terstruktur mengenai kepatuhan minum obat, pengaturan diet, aktivitas fisik, pembatasan cairan, pengenalan tanda bahaya, dan jadwal kontrol. Pengumpulan data menggunakan kuesioner Self-Care of Heart Failure Index dan Barthel Index. Analisis data dilakukan menggunakan uji Wilcoxon Signed Rank Test dengan tingkat kemaknaan α = 0,05. Sebelum edukasi discharge planning sebanyak 61,7% responden memiliki tingkat kemandirian sedang dan hanya 20,0% memiliki kemandirian tinggi. Setelah diberikan edukasi discharge planning, proporsi responden dengan tingkat kemandirian tinggi meningkat menjadi 71,7%. Hasil analisis menunjukkan terdapat pengaruh signifikan edukasi discharge planning terhadap peningkatan kemandirian pemenuhan kebutuhan dasar pasien gagal jantung (p = 0,001). Edukasi discharge planning berpengaruh signifikan terhadap peningkatan kemandirian pemenuhan kebutuhan dasar pasien gagal jantung. Pelaksanaan discharge planning yang komprehensif perlu diterapkan secara konsisten sebagai bagian integral pelayanan keperawatan untuk meningkatkan kualitas hidup pasien dan menurunkan angka rawat ulang. Kata Kunci: Discharge Planning, Gagal Jantung, Kemandirian, Self-Care, Edukasi Keperawatan